Differential Expression of Small Heat Shock Protein Genes Hsp23 and Hsp40, and heat shock gene Hsr-omega in Fruit Flies (Drosophila melanogaster) along a Microclimatic Gradient. - Carmel, J.; Rashkovetsky, E.; Nevo, E.; Korol, A. (Journal of Heredity, 2011)
We examined the role of small Hsp genes (Hsp23 and Hsp40) and heat shock gene Hsr-omega in the thermoadaptation of Drosophila melanogaster inhabiting a highly heterogeneous microsite (Nahal Oren canyon, Carmel massif, Israel). We tested whether interslope differences in Drosophila thermoadaptation, revealed in our previous studies, are associated with the differential expression of these genes. Our results demonstrate an increased expression of the Hsp40 gene in thermotolerant lines subjected to mild heat shock treatment (P < 10(-6), analysis of variance test). A high positive correlation was found between the levels of Hsp40 expression and scores of basal (R = 0.74; P < 0.001, based on the Spearman rank correlation test) and induced thermotolerance (R = 0.78; P < 0.0001), implying a significant contribution of Hsp40 gene in thermoadaptation.